UJI BEDA ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY AKIBAT PERISTIWA ASIAN GAMES 2018 JAKARTA-PALEMBANG (Studi pada Perusahaan yang Terdaftar dalam Indeks LQ-45 di BEI Tahun 2018) - Rahma Sugiharto Putra; Saparila Worokinasih; Ferina Nurlaily (Jurnal Administrasi Bisnis, 2020)
This study was conducted to determine whether there are differences in the average abnormal return and trading volume activity before and after the opening ceremony and closing ceremony of the Asian Games 2018. This study use the event study method. The population and sample in this study are company shares included in the LQ-45 Index from August 2018 to January 2019. The trading period is 12 trading days consisting of 3 days before the opening ceremony, 3 days after the opening ceremony of the Asian Games 2018 and 3 days before the closing ceremony, 3 days after the closing ceremony of the Asian Games 2018. Data analysis used Paired Sample t-Test and Wilcoxon Signed Rank Test. The results showed that there were no significant differences in the average abnormal return and trading volume activity in the period before and after the opening ceremony of the Asian Games 2018. However, there were significant differences in the average abnormal return and trading volume activity in the period before and after the closing ceremony of the Asian Games 2018. Kеywords: Asian Games, Mega Sport Event, Event Study, Abnormal Return, Trading Volume Activity.